Silver nanoparticles loaded pyrrole based pesticidal metabolites (AgNps-PFM) nanoconjugate induced impact on the gut microbion and immune response against lepidopteron pest Spodoptera litura (Fab.) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Pest control measures using nanobiotechnology principles is now being extensively utilized in the various parts of the world. Understanding the molecular mechanism behind the pestiicdal activity of the nanomaterials is essential to exploit the principles of nanomaterials as an effective pest control strategy. In the present investigation, impact of the nanoconjugate prepared from biogenic silver nanoparticles-fungal based insecticidal metabolites (AgNps-FM) on the gut microbion and immune response against major lepidopteron pest Spodoptera litura (Fab.) was studied. Nanoconjugate was prepared from silver nanoparticles from Pomegranate (Punica granatum) peel extract with the fungal based pesticidal metabolites. Highly stable nano structural nano conjugate thus obtained was evaluated against gut microbion and immune response of Spodoptera litura. Gut microbion status was studied by determination of microbial count, extra cellular enzymes potential of the gut microbial isolates adopting culture dependent methods. Nanoconjugate induced effect on the immune response was done by recording total hemocyte count and reduced total haemocyte count, phenol oxidase activity and lectin expression pattern Synthesized nanoconjugate brought about notable impact on the gut microbion count and their extra cellular enzyme potential. Reduced haemocytes count, poor lectin expression and reduced phenol oxidase production reveals the immune suppressive activity. High efficacy of the Nanoconjugate thus obtained would suggest the possible utilization of Nanoconjugate as an effective, safe pesticidal agent against economic important insect pests.